Peran Moderasi Kepemilikan Asing terhadap Hubungan Penjualan kepada Pihak Berelasi dengan Nilai Perusahaan - Nadiya; Ermad M J; Gebrina Ridzqy, Syiva (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to examine the role of foreign ownership in the relationship between sales to related parties and firm value. The population in this study are raw goods sector companies listed on the Indonesian Stock Exchange from 2021 to 2022, totaling 192 companies. The sample in this study was selected with certain criteria. The criteria are companies that have foreign ownership, make sales transactions to related parties, and are listed on the Indonesian Stock Exchange consecutively during the observation period. The final sample is 21 companies and with 42 observations. The data collection technique used in this research is documentation. The technique is to collect company financial report data and idx publication reports in the form of idx statistics yearly to find out the value of the company. The analytical method used in this study is moderated regression analysis with the EGLS (cross-section random effects) panel method with the help of the Eviews application. The results of this study found that sales to related parties had no significant effect on firm value. This can be seen from the significant value, which has a higher significant level (0.8374 > 0.05). Foreign ownership only has the potential to moderate (homologizer moderated) the relationship between sales to related parties and company value. This can be seen from the significant values of the interaction variables which are also greater than the significant level (0.7052 > 0.05).